PENGGARUH LATIHAN QUICK LEAP TERHADAP DAYA LEDAK OTOT TUNGKAI (EXPLOSIVE POWER) PEMAIN BOLA VOLI PUTRA PESANTREN TEKNOLOGI RIAU - Fajar Imam Sanyaja; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstark: The problem in this research is that when striking the ball it seems less like jumping. And when jumping is often not optimal due to weak leg muscle power, so opponents can easily find points when the conditions in the boarding school are from Riau volleyball players for men's technology. The title in this research is